2019
DOI: 10.1055/s-0039-1692449
|View full text |Cite
|
Sign up to set email alerts
|

Change in Shear Elastic Modulus of Thigh Muscle by Changing Muscle Length Using Ultrasound Shear Wave Elastography in Beagle Dogs

Abstract: Objectives This study investigated the relationship between the change in the shear elastic modulus and the change in muscle length using ultrasound shear wave elastography. Study Design Four thigh muscles, cranial part of the sartorius, vastus lateralis, biceps femoris and semitendinosus muscles, of 21 pelvic limbs in 12 clinically healthy Beagle dogs were used. The muscle length was estimated using a radiograph and the flexed and extended positions of the coxofemoral and stifle joints, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Various recent veterinary investigations have shown that in dogs, 2-D SWE can be applied for the estimation of stiffness in normal parenchyma of the liver, spleen, kidneys, pancreas, prostate, lymph nodes, submandibular salivary gland, thyroid (12,13), postpartum uterine wall (14), small intestinal wall (15), and thigh muscle (16). Moreover, several studies attempted to compare abnormal lesions of the liver, pancreas, and kidneys with those of normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…Various recent veterinary investigations have shown that in dogs, 2-D SWE can be applied for the estimation of stiffness in normal parenchyma of the liver, spleen, kidneys, pancreas, prostate, lymph nodes, submandibular salivary gland, thyroid (12,13), postpartum uterine wall (14), small intestinal wall (15), and thigh muscle (16). Moreover, several studies attempted to compare abnormal lesions of the liver, pancreas, and kidneys with those of normal animals.…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, sonoelastography, a non-invasive ultrasound-based technique to assess tissue stiffness, is highly sensitive to detect the difference in stiffness in healthy versus diseased testicles and has shown some promise in veterinary medicine; in particular, different levels have been observed of stiffness in the case of inflammatory and neoplastic disorders, with the highest stiffness observed in cases of malignant lesions [ 19 , 20 ]. This technique has also been proved to be useful to be applied to measure kidney stiffness in cats in the case of chronic kidney disease or to the detect canine liver fibrosis in a non-invasive way; furthermore, it is also potentially appliable in cases of musculoskeletal disorders [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound shear wave elastography (SWE) is a reproducible and non-invasive method for measuring tissue elasticity [1]. An ultrasound system with SWE software installed and a highfrequency linear array transducer are required to perform measurements.…”
Section: Introductionmentioning
confidence: 99%